KARAKTERISTIK DAN KENYAMANAN IKLIM LOKASI WISATA BERBASIS ALAM DI ECO-PARK ANCOL, KEBUN RAYA BOGOR DAN KEBUN RAYA CIBODAS - Nofi Yendri Sudiar; Yonny Koesmaryono; Perdinan Perdinan; Hadi Susilo Arifin (Universitas Lambung Mangkurat, 2019)
This research explores the characteristics and comfort of climate in nature-based tourism areas in Ancol Eco-Park (EPA) (3masl), Bogor Botanical Gardens (KRB)(260 masl) and Cibodas Botanical Gardens (KRC) (1340 masl). Climate characteristics use the Schmidt-Ferguson and Koppen classifications. Calculation of climate comfort scores using TCI and HCI methods and modifying the thermal aspects. In addition to surveys with questionnaires, measurements of temperature, humidity and wind speed were carried out in all three regions simultaneously. Climate classification according to Schmidt-Ferguson obtained by KRB is type A climate, EPA and KRC are type C climate. Classification according to Koppen, the three regions include the climate of the tropical rainforest namely EPA (Am), KRB and KRC (Af). The vegetation component dominates the three tourist areas with a percentage of over 60% of the tourist areas. The climate comfort index based on calculations results in a comfortable KRC area throughout the year while EPA and KRB are comfortable in the dry season. Comparison of comfort index based on calculations with visitor perceptions results in thermal aspects for the tropics needing to be modified. From 12:00-12:59 WIB to 13:00-13:59 WIB, the most uncomfortable hours of the day. Temperature intervals with comfortable categories are 25.2°C - 29.0°C or effective temperatures between 20.5°C - 24.6°C.